2020
DOI: 10.20527/jpkmi.v6i3.8179
|View full text |Cite
|
Sign up to set email alerts
|

Komparasi Efektivitas Media Audiovisual Dan Media Audio Terhadap Pengetahuan Dan Motivasi Remaja Putri Untuk Melaksanakan Pemeriksaan Payudara Sendiri (Sadari)

Abstract: ABSTRAKBerbagai laporan menunjukkan terjadinya peningkatan kasus kanker payudara dari tahun ke tahun pada wanita usia subur. Seiring dengan itu, terdapat pola peningkatan pengidap kanker payudara pada usia remaja. Salah satu langkah untuk mendeteksi secara dini kemungkinan seseorang mengidap kanker payudara adalah dengan melakukan pemeriksaan payudara sendiri. Sayangnya, pengetahuan dan motivasi untuk melakukan SADARI di kalangan wanita remaja masih rendah. Penelitian ini fokus pada komparasi efektivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 3 publications
(4 reference statements)
0
2
1
3
Order By: Relevance
“…The work of Deviani and colleagues (2019) also supports this study'sfindings; considering breast self-examination, that study showed that education using audio-visual media influenced knowledge more than audio media alone. 13 However, this study's results do not follow those of the study conducted by Kasman and colleagues (2017), which found that leaflet media was more effective in increasing knowledge than video media; however, that study did show that video media produced a difference in knowledge before and after health education with a p-value of 0.004. 14 In contrast, research by Ibe and Abamuche (2019) produced similar results to this study, finding that the group exposed toaudio-visual learning increased their test scores, suggesting that teachers can use audiovisual technology media to deliver learning material.…”
Section: Discussioncontrasting
confidence: 97%
“…The work of Deviani and colleagues (2019) also supports this study'sfindings; considering breast self-examination, that study showed that education using audio-visual media influenced knowledge more than audio media alone. 13 However, this study's results do not follow those of the study conducted by Kasman and colleagues (2017), which found that leaflet media was more effective in increasing knowledge than video media; however, that study did show that video media produced a difference in knowledge before and after health education with a p-value of 0.004. 14 In contrast, research by Ibe and Abamuche (2019) produced similar results to this study, finding that the group exposed toaudio-visual learning increased their test scores, suggesting that teachers can use audiovisual technology media to deliver learning material.…”
Section: Discussioncontrasting
confidence: 97%
“…Hal ini sejalan dengan penelitian serupa yang menemukan terdapat pengaruh media audiovisual dan media audio terhadap pengetahuan dan motivasi remaja melakukan SADARI. Media audio visual lebih efektif dibandingkan dengan media audio terhadap perilaku melakukan SADARI (Deviani, Asyary and Edmi Edison, 2020). Namun, berbeda dengan hasil penelitian lain yang menunjukkan bahwa terdapat hubungan antara pengetahuan dan perilaku SADARI, mayoritas responden mendapatkan informasi SADARI dari teman sebaya sebanyak 55% (Nurrohmah and Yati, 2019).…”
Section: Hasil Dan Pembahasanunclassified
“…Adapun metode edukasi yang diberikan sebaiknya dengan menggunakan audiovisual yang lebih efektif ketimbang audio saja seperti edukasi satu arah. 12 Mengingat besarnya prevalensi pengidap stroke di Indonesia, maka upaya promosi tersebut seyogyanya tidak sebatas kala pasien datang berobat ke puskesmas, namun perlu dilakukan kunjungan ke rumahrumah atau di melalui Program Indonesia Sehat dan Pendekatan Keluarga sebagai wadah sosialisasi.…”
Section: Pembahasanunclassified